Power-Aware Routing for Underwater Wireless Sensor Network - Nguyen, Thanh Tung (Springer International Publishing Switzerland, 2017)
International Conference on Context-Aware Systems and Applications ICCASA 2013: Context-Aware Systems and Applications pp 97-101